2023
DOI: 10.1108/jmtm-07-2022-0254
|View full text |Cite
|
Sign up to set email alerts
|

Driving forces for industry 4.0 readiness, sustainable manufacturing practices and circular economy capabilities: does firm size matter?

Abstract: PurposeDespite just eight years remaining to meet the sustainable development goals (SDG, 2030), the manufacturing industry faces numerous challenges for small and medium-sized enterprises (SMEs). Some notable challenges include integrating sustainability, circular economy (CE), and industry 4.0 (I4.0) technologies in a productive manner. However, there is a paucity of evidence available on the role of institutional pressures and organizational resources to promote I4.0 and sustainability. To fill this void, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 82 publications
(219 reference statements)
1
2
0
Order By: Relevance
“…This requires new retail enterprises to scientifically analyse consumers' consumable content and implementation process and improve the matching degree of system and user needs. Furthermore, the current study also found that all mediated paths were supported , 2023b).…”
Section: Discussion and Findingssupporting
confidence: 74%
“…This requires new retail enterprises to scientifically analyse consumers' consumable content and implementation process and improve the matching degree of system and user needs. Furthermore, the current study also found that all mediated paths were supported , 2023b).…”
Section: Discussion and Findingssupporting
confidence: 74%
“…Meanwhile, Nor-Aishah et al (2020) and Hanaysha et al (2022) measured the sustainable performance of SMEs in a holistic manner, which consisted of three aspects known as economic, environmental and social sustainability. In some other previous studies, researchers focused on the adoption of "lean and green thinking" in achieving efficiency in production and reducing waste (Caldera et al, 2019), implementation of "lean thinking" in directing business firms towards sustainability practices (Franco & Rodrigues, 2021), application of "lean-green operations" in new product development for efficiency (Oliveira et al, 2022), green manufacturing practices and green innovation for corporate sustainable performance (Al-Hakimi et al, 2022), sustainable product and process design, sustainable waste disposal management, sustainable human resource management and local community development (Mitra, 2023) and, performing sustainable manufacturing practices which focused on using economically-sound processes to reduce negative environmental impacts in products production (Ali & Johl, 2023). It could be said that although many organizations have adopted sustainable practices, there remains no uniformed reporting standard and measurement of sustainable performance in which firms measure different things and report in different ways (Byrne, 2023;Ribeiro, 2023).…”
Section: Entrepreneurship and Sustainability Issuesmentioning
confidence: 99%
“…Global supply chain complexities have attracted a lot of attention recently, and they have been exacerbated by the pandemic, its economic fallout, and the recent Ukraine conflict [1]. These incidents have clearly demonstrated the vulnerability of modern supply chains, prompting a recent report from McKinsey & Company that highlighted their growing complexity and the integration of sustainability considerations [2].…”
Section: Introductionmentioning
confidence: 99%